Factors of competitiveness of the enterprise - Amirbekuly, Yе.; Ukubasova, G.S.; Kaskin, Т.Т. (BUKETOV BUSINESS REVIEW, 2017)
This article explores the factors that affect the competitiveness of an industrial enterprise. The complicated processes of reforming economic relations and the development of new market conditions in our country require new approaches to the organization of production and economic activities, principles and methods of production management. In the course of economic reforms, Kazakhstan's industrial enterprises have undergone significant changes, both from the point of view of the socio-economic nature of ownership, and from the qualitative and quantitative characteristics of their production capacities. The fundamentally changed external environment required the skills of doing business in a highly competitive environment. Factors are those phenomena and processes of production and economic activity of the enterprise and the socio-economic life of society that cause a change in the absolute and relative magnitude of production costs, and as a result, a change in the level of competitiveness of the enterprise itself. The key factors of market success include: the financial situation of the enterprise, the development of the base for its own research works, and the level of expenditure on the; the availability of advanced technology, the provision of highly skilled personnel, the ability of production (and price) maneuvering, the availability of a sales networking and experienced marketing personnel, the state of technical service, the opportunities to credit their exports (including the help of state organizations), the effectiveness of advertisement and public relations system, security information, the creditworthiness of the major buyers. Factors can affect both towards improving the competitiveness of enterprises and downwards. Factors promote the conversion of opportunities into reality. Factors determine the means and ways of using reserves of competitiveness.